Two‐Color Passively Q‐Switched Raman Microchip Laser with Tunable Power Intensity Ratio and Elliptical Polarization. Issue 5 (17th March 2022) - Yang, Haolin; An, Yinming; Chen, Dimeng; Dong, Jun
Abstract: Elliptically polarized high peak power two‐color lasers have potential applications on material science, biology, optical detection, and terahertz wave generation. Two‐color pulsed lasers with flexible power intensity ratio are essential for analyzing material properties, however, control of power ratio between two lasers is a challenge for developing compact passively Q‐switched (PQS) solid‐state laser. Here, taking advantage of Nd:YAG/Cr 4+ :YAG composite crystal and a ‐cut YVO4 crystal, a PQS Raman microchip laser is developed for generating a two‐color Raman laser with tunable power intensity ratio between two Raman lasers and elliptical polarization. Power intensity ratio tuned from 1 to 0 between 1166 nm Raman laser and 1166/1176 nm two‐color laser is achieved by adjusting a ‐cut YVO4 crystalline orientation. State of polarization of Raman laser is elliptical polarization. The ellipticity is flexibly tuned from 0.3 to 0.91 by adjusting pump power and a ‐cut YVO4 crystalline orientation. The Raman laser pulses with peak power of 6.4 kW and pulse width of 1.5 ns are obtained. The synchronized Raman laser pulse repetition rate is 14.3 kHz. This work enables development of a compact high peak power two‐color Raman laser with flexible control of power intensity ratio between two color lasers in a diode pumped PQS Raman microchip laser. Abstract : Elliptically polarized two‐color Raman laser with tunable power intensity ratio between 1166 and 1176 nm Raman lasers is generated in a diode pumped Nd:YAG/Cr 4+ :YAG/YVO4 passively Q‐switched Raman microchip laser. Raman laser pulses with pulse width of 1.5 ns and peak power of 6.4 kW are achieved.